2014
DOI: 10.1111/bph.12864
|View full text |Cite
|
Sign up to set email alerts
|

Simulation with cells in vitro of tamoxifen treatment in premenopausal breast cancer patients with different CYP2D6 genotypes

Abstract: BACKGROUND AND PURPOSETamoxifen is a prodrug that is metabolically activated by 4-hydroxylation to the potent primary metabolite 4-hydroxytamoxifen (4OHT) or via another primary metabolite N-desmethyltamoxifen (NDMTAM) to a biologically active secondary metabolite endoxifen through a cytochrome P450 2D6 variant system (CYP2D6). To elucidate the mechanism of action of tamoxifen and the importance of endoxifen for its effect, we determined the anti-oestrogenic efficacy of tamoxifen and its metabolites, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
3
23
0
2
Order By: Relevance
“…The antiestrogenic activities of tamoxifen and metabolites can be different when investigated in different cell lines, or in the presence of estrogen concentrations [31, 32]. However, the in vitro experiments were conducted to obtain the relative antiestrogenic activities of tamoxifen and three metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The antiestrogenic activities of tamoxifen and metabolites can be different when investigated in different cell lines, or in the presence of estrogen concentrations [31, 32]. However, the in vitro experiments were conducted to obtain the relative antiestrogenic activities of tamoxifen and three metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…13) to view these data based on the results previously discussed in the section describing the drift in cell populations in vitro if estrogen induced apoptosis is blocked by an inhibitor of cSrc. The principle of improving the antiestrogenic mixture of metabolites in both a premenopausal and postmenopausal patient environment has recently been modeled in vitro (194, 195). These studies represent the immediate effects of tamoxifen and metabolites of estrogen stimulated growth and gene regulation.…”
Section: Summary and Future Clinical Perspectivementioning
confidence: 99%
“…27,28) Using immunohistochemistry, we found that CYP2D6 protein was localized in the enterocytes and lamina propria of the small intestine of Japanese individuals. Although CYP2D6 mRNA levels were lower than the CYP3A4 mRNA levels in the samples, we did find that CYP2D6 mRNA was expressed in the small intestine of Japanese individuals.…”
Section: Discussionmentioning
confidence: 94%